2020
DOI: 10.3390/tropicalmed5020084
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Insecticide Susceptibility in Aedes Aegypti Populations from the Two Biggest Cities, Ouagadougou and Bobo-Dioulasso, in Burkina Faso: Implication of Metabolic Resistance

Abstract: In West Africa, Aedes aegypti remains the major vector of dengue virus. Since 2013, dengue fever has been reemerging in Burkina Faso with annual outbreaks, thus becoming a major public health problem. Its control relies on vector control, which is unfortunately facing the problem of insecticide resistance. At the time of this study, although data on phenotypic resistance were available, information related to the metabolic resistance in Aedes populations from Burkina Faso remained very scarce. Here, we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…aegypti is known to be occur worldwide (Moyes et al, 2017) but its arrival in West Africa is relatively recent in Senegal (Sene et al, 2021), in Ghana (Kawada et al, 2016), and Cote d'Ivoire (Konan et al, 2021). Recent studies by Badolo et al (Badolo et al, 2019), Namountougou et al (Namountougou et al, 2020), and Sombie (Sombie et al, 2019) have reported resistance to both pyrethroid I and II types in the two largest cities, Ouagadougou and Bobo‐Dioulasso. Burkina Faso has no history of pyrethroids used against in Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti is known to be occur worldwide (Moyes et al, 2017) but its arrival in West Africa is relatively recent in Senegal (Sene et al, 2021), in Ghana (Kawada et al, 2016), and Cote d'Ivoire (Konan et al, 2021). Recent studies by Badolo et al (Badolo et al, 2019), Namountougou et al (Namountougou et al, 2020), and Sombie (Sombie et al, 2019) have reported resistance to both pyrethroid I and II types in the two largest cities, Ouagadougou and Bobo‐Dioulasso. Burkina Faso has no history of pyrethroids used against in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports investigating the susceptibility of Ae. aegypti in Burkina Faso, suggested that they are highly resistance to pyrethroids, moderately resistance to carbamates but remain susceptible to organophosphate insecticides (Badolo et al, 2019, Namountougou et al, 2020, Sombie et al, 2019). Here, we provide recent data on resistance to the main insecticide classes status in Ae.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti , and their insecticide susceptibility, in rural, suburban, and urban sites in different ecological zones of Ghana. In addition to identifying targets and options for control, the results will also aid the development of a surveillance system for Aedes as vectors of arboviruses for the planning of disease control in Ghana [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, apart from one study performed in Burkina Faso, no other report on Ae . aegypti detoxification genes expression exists for other West African countries [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%